The Efforts to Improve Social Studies Learning Outcomes Using Role Playing Models for Class II Students at Elementary School 4 Pahandut - Handayani, Dwi Indah; Setyawan, Dedy; Munandar, Haris; Juhairiah, Siti (International Journal of Universal Education, 2023)
This study aims to: 1) To describe the learning activities of students in social studies learning by using the Role Playing model in class II Elementary School 4 Pahandut. 2) To improve student learning outcomes in social studies learning by using a role playing model in class II Elementary School 4 Pahandut.This type of research is Classroom Action Research (CAR), with the research subject of all students of class II Elementary School 4 Pahandut totaling 6 students. Data collection techniques in this study using tests and observations. Data analysis used qualitative and quantitative data analysis. The results of this study indicate that: 1) the social studies learning activity of the second grade students of Elementary School 4 Pahandut cycle I with an average of 3.25 while the social studies activity of the second grade students of Elementary School 4 Pahandut Cycle II with an average of 3.30. 2) the learning outcomes of class II students at Elementary School 4 Pahandut increased from the average pre-test score of 58.3, with classical completeness 33.3%, while the post-test results in the first cycle averaged 66.6 with classical completeness 50%, while the results of the second cycle post-test an average value of 86.6 with 100% classical completeness.